Comparative Analysis of Existing Contracts for Building Information Modelling (BIM) Projects in Malaysia and Selected Common Law Countries - Raja Khadijah Raja Berema, Zulhabri Ismail, Juliana Brahim, (International Journal of Sustainable Construction Engineering and Technology, 2022)
The Malaysian construction scene has been striving forward towards modernisation since the mention of Vision 2020. It includes innovative prowess in technology as it reaches Construction 4.0 within the field. Building Information Modelling (BIM) has been an alternative towards some of the long-standing issues. However, its adoption remains slow despite the potential for an integrative collaboration within projects. The unreceptive drive is said to be associated with contractual setbacks which hold back the adoption. The existing standard form of contracts is with the view which lacks facilitation towards BIM’s specific roles, process and outcome. Hence, a necessity arises for the need to include changes towards the incorporation of BIM. This study employs a narrative literature review using a systematic review approach using the terms BIM, contract, BIM contract, procurement, legal, and contractual problems. This paper, therefore, is with the aim of a comparative analysis of existing contractual provisions for Malaysia against other selected common law countries. The contractual discrepancy observed in BIM's legality has already been resolved by developed countries namely the United Kingdom and Singapore for contract administration success. Nonetheless, the status of the construction industry remains contentious in Malaysia..